Leo George Hertlein (1898-1972) - Aurele La Rocque (Hello World!, 1972)
The October 1970 number of the Nautilus (vol. 84, no. 2) was subtitled the Leo George Hertlein Honor Issue by his friends who contributed a biographic sketch, a list of taxa proposed in his honor, a bibliography of his works, a list of names proposed by him, and papers on Mollusca, particularly the marine forms of the West Coast of the Americas which were the main field of his scientific endeavors.